Follow-up OAUNI photometry of SN2022hrs - Pereyra, Antonio (2022)
We report additional multiband photometry of Type Ia SN2022hrs (TNSTR-2022-994, TNSCR-2022-997, ATel #15378) on 2022-07-01 (UT) gathered with the OAUNI 51cm telescope (Pereyra et al. 2015; arXiv:1512.03104) at Huancayo Observatory, Peru. CCD imaging using BVRI filters was performed under non-photometric conditions (seeing ~2.1") and airmass lower than 1.9. Total integration times of (60x20s=1200s) for V, R and I filters, and (90x20s=1800s) for B filter yielded: Date (UT) filter mag 2022-07-01.111 B 15.94 +/- 0.05 2022-07-01.042 V 15.04 +/- 0.01 2022-07-01.062 R 15.00 +/- 0.01 2022-07-01.086 I 15.16 +/- 0.02. UCAC4 field stars (508-055361 and 508-055359) were used for the zero point calibration. Following the GELATO classification (TNSCR-2022-997), our measurements are approximately two months after the maximum brightness. The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).